Gorontalo local rice plant response which planted with the lowland system and upland system. Issue 1 (April 2020) - Buri, N; Riadi, M; Dungga, N E; Hipi, A; Mantau, Z
Abstract: The development of upland rice cultivation is a strategic effort to support and increase national rice production. Local superior cultivars have long been cultivated by farmers through generations through various efforts and instincts in their possession by utilizing genetic diversity to obtain superior characters and adapt well to local agro-ecology. The research aims to obtain Gorontalo local rice genotypes that can grow and produce both on upland and lowland fields. The study was conducted in Bulotalangi Village, East Bulango Subdistrict, Bonebolango District, Gorontalo Province. Located at an altitude of 80 m above sea level, an average rainfall of 1, 485 mm per year, soil texture of sandy loam and pH of 5.5. The research was conducted from October 2017 to March 2018. This study used a randomized block design with three replications. The treatment consisted of 10 genotype treatments namely Situbagendit, Pulo Putih, Maraya, Bokungo, Monu Genja, Buruna, Yenti, Boleyara, Ponda and Bolotonu. The results show that the adaptive genotype grew and had a high and good production to be developed in the upland and paddy fields, namely the Maraya genotype (4.10 tons.ha −1 ), the Situbagendit genotype (3.73 tons.ha −1 ), the Yenti genotype (4.10 tons.ha −1 ) 3.26 tons.ha −1 ), and Bolotonu genotype (3.08 tons.ha −1 ).